2010
DOI: 10.1366/000370210791114248
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Protoporphyrin Fluorescence as a Potential Marker of Diabetes

Abstract: Protoporphyrin (PpIX), a porphyrin derivative, is the intermediate metabolic precursor of the heme molecule. Abnormal metabolism of total erythrocyte PpIX has been observed in diseases such as cancer, lead poisoning, psoriasis, iron deficiency anemia and acute porphyries. Diabetes mellitus (DM) is a complex metabolic syndrome in which hyperglycemia is the primary clinical manifestation and contributes to the diabetic complications. The aim of this study was to evaluate the utility of fluorescence spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Lead and other heavy metal intoxication [15][16][17] and a variety of sideroblastic [18] and inherited microcytic anemias [19] may also be responsible for alterations in erythrocyte PPIX and ZnPP. A recent study found decreased PPIX fluorescence in erythrocytes from diabetic compared to non-diabetic mice, suggesting the possible use of PPIX as a diagnostic marker for monitoring of diabetes [20]. In addition to their diagnostic utility, measurements of PPIX and ZnPP may be useful in following the effects of therapy on iron deficiency, the course of chronic disorders [9], and some forms of porphyria.…”
Section: Introductionmentioning
confidence: 99%
“…Lead and other heavy metal intoxication [15][16][17] and a variety of sideroblastic [18] and inherited microcytic anemias [19] may also be responsible for alterations in erythrocyte PPIX and ZnPP. A recent study found decreased PPIX fluorescence in erythrocytes from diabetic compared to non-diabetic mice, suggesting the possible use of PPIX as a diagnostic marker for monitoring of diabetes [20]. In addition to their diagnostic utility, measurements of PPIX and ZnPP may be useful in following the effects of therapy on iron deficiency, the course of chronic disorders [9], and some forms of porphyria.…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that this fluorescence is actually due to the formation of a hemoglobin photoproduct (Shirshin et al, 2018;Wu et al, 2020), as native hemoglobin alone is nonfluorescent at single photon excitation due to ultrafast electron transfer to heme's iron atom (Qiqi et al, 2015;Tripathy & Steer, 2007). However, porphyrins like heme precursors and other derivatives do possess inherent fluorescence when lacking the quenching iron atoms, typically exhibiting emission peaks in the 620-635 nm range when excited at 405 nm (Fauaz et al, 2010) (Figure 2c,d). This porphyrin fluorescence is especially notable when the Wetlaufer, 1963), (b) Emission spectra (redrawn from Albani, 2004) of aromatic amino acids tryptophan, tyrosine, and phenylaniline.…”
Section: Different Components Of the Blood And Their Source Of Autofl...mentioning
confidence: 99%
“…(c) Excitation spectra and (d) emission spectra of collagen (black), elastin (blue), porphyrins (red), lipo-pigments (cyan) and pyridoxine (green) (redrawn from Wagnieres et al, 1998). (e) Absorption (dotted line) and emission (solid line) spectra of NADH (red) and FAD (blue) (redrawn from Islam et al, 2013) molecules have been extracted from RBCs with a solvent like acetone (Fauaz et al, 2010;Masilamani et al, 2004). Thus, while hemoglobin is a dominant contributor due to heme in autofluorescence of RBC and can be excited at ~438 nm, porphyrin is another source which can be excited at ~405 nm.…”
Section: Different Components Of the Blood And Their Source Of Autofl...mentioning
confidence: 99%
See 2 more Smart Citations